DEPICTION OF LEGAL REALITY IN INDIAN JUDICIAL SYSTEM IN HINDI LITERATURE - Mishra, Om (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Dard-e-Dakhila As the name suggests, injustice was done to a person in admission to the university. The university administration includes professors, department heads, deans, campus deans, examination department, registrar, vice chancellor, all. On the other hand, in judicial administration, judges of the High Court, Supreme Court and lawyers, who are officers of the court, all have appeared with their basic characters. The real satire on the condition of Indian universities is visible in the following lines- "Is this a system? Is it right to call it a system? Is it not the responsibility of the college or the department head to immediately send such information to the concerned department of the university? Is it not the responsibility of the examination department to contact the concerned college or department itself and find out what happened to the supplementary of a certain student? Without passing the supplementary, within the prescribed period, will any college accept the fee of a student? Will any department allow him to join the class? Will any college issue him a roll number, not once, but thrice, to appear in the second, third and final session examination? Will any college release the mark sheet to a student just like that, without fully satisfying itself? And many such questions had raised the trumpet of a tremendous rebellion within justice against the system. In the midst of this rebellion, he reached home.''1